Peranan Advokat Dalam Memberi Jasa Hukum Pada Lingkungan Peradilan: A. Peran Advokat dalam Memberi Jasa Hukum B. Peran Advokat dalam Memberi Jasa Hukum Pada Lingkungan Peradilan Agama C. Peran Advokat dalam Memberi Jasa Hukum Pada Lingkungan Peradilan Negeri D. Peran Advokat dalam Memberi Jasa Hukum Pada Lingkungan Peradilan Tata Usaha Negara E. Peran Advokat dalam Memberi Jasa Hukum Pada Lingkungan Peradilan Militer - Lubis, Fauziah; Lubis, Anisah; Mardhyah, Dwi Putri; Dwi Khoironi, Sri; Ariq Nst, Naufal; Ali Hutapea, Saidin (TERAJU: Jurnal Syariah dan Hukum, 2025)
This research aims to analyse the role of advocates in providing legal services in various judicial environments in Indonesia, including religious, state, state administration, and military. The background of this research is based on the importance of advocates as an integral part of the legal system that bridges society with judicial institutions, as well as being an enforcer of the rule of law, justice, and human rights. The issue raised is the extent to which advocates are able to carry out their role effectively in various courts. The method used is normative juridical with a statutory approach (statute approach) and literature analysis to explore the relevant legal framework. Research results show that advocates have a great responsibility not only in defending the client, but also in ensuring the fulfilment of the community's constitutional rights, including through free legal assistance (pro bono). However, the main challenge lies in the limited scope of advocates in the military judiciary. In conclusion, advocates play an important role as a balancer of power in the legal system. Strengthening the legal framework is needed so that advocates can contribute more widely, ensuring a fair, transparent, and just judicial process.